Chronic Tenosynovitis due to Mycobacteria kansasii in an Immunocompetent Host - Michael S. Wang; Michael Berry; Alissa Lehto-Hoffman; Linh Vi; Nina Ramessar (Case Reports in Infectious Diseases)
We report a case of a healthy 56-year-old male who presented with chronic swelling and erythema in his right hand. He had a prior chemical exposure several years ago and subsequent exposure to freshwater, fish tank, and soil. Laboratory data showed a slightly elevated CRP. An MRI was consistent with suggestive of flexor tenosynovitis. He underwent surgical debridement and was diagnosed with Mycobacterium kansasii. He was treated with clarithromycin, rifampin, and isoniazid, but subsequent susceptibility testing revealed resistance to isoniazid. Isoniazid was switched to ethambutol, but further susceptibility testing also suggested resistance to ethambutol. Antimicrobial therapy was stopped at 6 months due to clinical recovery, and the patient is currently doing well as of 6 months postdiscontinuation of therapy.